2009
DOI: 10.1111/j.1365-2222.2009.03229.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene‐expression profiles in human nasal polyp tissues and identification of genetic susceptibility in aspirin‐intolerant asthma

Abstract: These results indicate that INDO and IL1R2, which were identified from gene expression analyses of nasal polyps in AIA, represent susceptibility genes for AIA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…It has recently been shown that the innate immune system has considerable specificity and the ability to discriminate between pathogens and self. Previous studies of NP using cDNA microarray technology have identified differentially expressed genes involved with inflammatory processes on a ‘global’ level [3,4] and components of adaptive immunity in particular [5,6,7]. In contrast with these studies, the aim of this exploratory study was to determine if there were any differentially expressed genes in NP of nonatopic CRS patients that were associated with TLRs and their signaling elements.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…It has recently been shown that the innate immune system has considerable specificity and the ability to discriminate between pathogens and self. Previous studies of NP using cDNA microarray technology have identified differentially expressed genes involved with inflammatory processes on a ‘global’ level [3,4] and components of adaptive immunity in particular [5,6,7]. In contrast with these studies, the aim of this exploratory study was to determine if there were any differentially expressed genes in NP of nonatopic CRS patients that were associated with TLRs and their signaling elements.…”
Section: Discussionmentioning
confidence: 66%
“…Studies using cDNA microarray technology have identified differentially expressed genes involved with inflammatory processes on a ‘global’ level [3,4] and, in particular, components of adaptive immunity [5,6,7]. However, innate immune responses in the sinonasal mucosa in CRS have not been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that IL-1R2 was detectable in microarrays of whole lung tissue (IL-1R2 expression was "present" in 98.8% of subjects). IL-1R2 has been shown to be associated with aspirin-induced asthma, both at the level of gene expression in human nasal polyps and as SNP associations (68). In another study, IL-1R2 SNPs were associated with atopy and showed interaction with early childhood virus infection (69).…”
Section: Discussionmentioning
confidence: 94%
“…This is the first description of an association of IL1R2 polymorphisms with atopy and the first report of rs740044 in the context of asthma-related phenotypes, although a previous study of a Japanese population demonstrated association of an IL1R2 polymorphism with aspirin hypersensitivity in asthmatic patients. 46 This same polymorphism was identified as interacting with picornavirus infection (Table IV) to modify the risk for atopic asthma in children from the CAPPS cohort.…”
Section: Discussionmentioning
confidence: 94%